Cricket ball trauma causing temporal space abscess: Report of a case - Waknis P; Sabhlok S; Deshpande R (Wolters Kluwer Medknow Publications, 2010)
A 9-year-old boy reported with swelling on right side of the face after injury by a cricket ball while fielding. There was a history of hot fermentation after which the swelling increased in size leading to a temporal space abscess. The patient underwent incision and drainage with uneventful healing and was followed-up for a period of 7 years.